2000
DOI: 10.1785/0119990143
|View full text |Cite
|
Sign up to set email alerts
|

Envelope Broadening of Outgoing Waves in 2D Random Media: A Comparison between the Markov Approximation and Numerical Simulations

Abstract: Observations of seismic waves from earthquakes at depths between 100 and 200 km beneath Japan show that the initial portion of the S-wave arrival has greater duration than can be accounted for by earthquake source-time duration. The observed long duration of S waves has been explained as being caused by multiple forward scattering around the ray path between source and receiver. Array observations of Lg waveforms have also shown that multiple forward scattering along the path between the source and receiver ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 35 publications
5
57
0
Order By: Relevance
“…theoretically solved the envelope broadening of spherically outgoing waves in von Kármán-type 3-D random media that have a realistic power-law spectrum at large wavenumbers. Fehler et al (2000) confirmed the validity of the Markov approximation for scalar waves from a comparison with finite difference simulations in 2-D random media. Wegler et al (2006) numerically examined the applicable range of the Markov approximation, and the radiative transfer solution with Born scattering amplitudes and that with isotropic scattering for scalar waves taking the finite difference simulation envelope as a reference in 2-D random media.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…theoretically solved the envelope broadening of spherically outgoing waves in von Kármán-type 3-D random media that have a realistic power-law spectrum at large wavenumbers. Fehler et al (2000) confirmed the validity of the Markov approximation for scalar waves from a comparison with finite difference simulations in 2-D random media. Wegler et al (2006) numerically examined the applicable range of the Markov approximation, and the radiative transfer solution with Born scattering amplitudes and that with isotropic scattering for scalar waves taking the finite difference simulation envelope as a reference in 2-D random media.…”
Section: Introductionsupporting
confidence: 67%
“…According to Fehler et al (2000), we first define the TFMCF as the correlation of field U between two locations r θ and r θ within a small distance from the global ray direction θ =0 on the transverse line at distance r at different angular frequencies ω and ω , 2 (r, θ , θ , ω , ω where…”
Section: Markov Approximation For the Two-frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…Sato, Fehler, and Wu, 2002;Pride et al, 2003). We have used numerical modeling of wave propagation through random media along with various analytical approaches to better understand what characteristics of the medium can be inferred from analysis of seismic traces (Fehler, Sato, and Huang, 2000;Saito et al 2003;Sat0 et al, 2003). We have recently been investigating an approach for using AVO analysis to characterize the spatial heterogeneity in a layer.…”
Section: Random Media Characterization and Avo Analysismentioning
confidence: 99%
“…We have also used some of these methods for modeling primary forward wave propagation in random media Huang and Fehler, 1998b;Fehler et al, 2000). In this paper, we present an overview of these dual-domain migration methods.…”
Section: Introductionmentioning
confidence: 99%